2019
DOI: 10.1002/slct.201904004
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Alcohols Catalyzed by Supported Nano‐Au Catalysts

Abstract: A series of Cu‐containing trimetal mixed oxides supported nano‐Au catalysts were prepared and characterized by XRD, N2 sorption, elemental analysis and H2‐TPR. Then, their catalytic performance was firstly investigated in the selective oxidation of glycerol with 3% H2O2 or O2 as oxidants. It was found that both the elemental components of mixed oxides and the types of oxidant influenced remarkably the catalytic performance of the supported catalysts and the product distributions. Under the optimal reaction con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This agrees very well with the literature that the primary dehydrogenation of glycerol (C–H bond cleavage to form glyceraldehyde in Figure ) and the subsequent structural rearrangement are the dominant reaction pathways in the presence of non-noble metal systems. , In other words, weak oxidation activity (primary oxidation) of non-noble oxides preferably favors the formation of LA over deep oxidation products such as GLYA and glycolic acid. Deep (secondary) oxidation of glyceraldehyde to GLYA has been generally known to be poor over Cu and Ni catalysts, even in the presence of externally added O 2 . , In this work, however, it is surprising to observe that all four non-noble metal catalysts display 9.6–14.2% selectivity for GLYA, even in the absence of external O 2 . It corresponds to remarkable 0.74–1.66 mol·g·mol –1 ·h –1 deep oxidation rate, which exhibits a leading performance compared with literature data (Table S1).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…This agrees very well with the literature that the primary dehydrogenation of glycerol (C–H bond cleavage to form glyceraldehyde in Figure ) and the subsequent structural rearrangement are the dominant reaction pathways in the presence of non-noble metal systems. , In other words, weak oxidation activity (primary oxidation) of non-noble oxides preferably favors the formation of LA over deep oxidation products such as GLYA and glycolic acid. Deep (secondary) oxidation of glyceraldehyde to GLYA has been generally known to be poor over Cu and Ni catalysts, even in the presence of externally added O 2 . , In this work, however, it is surprising to observe that all four non-noble metal catalysts display 9.6–14.2% selectivity for GLYA, even in the absence of external O 2 . It corresponds to remarkable 0.74–1.66 mol·g·mol –1 ·h –1 deep oxidation rate, which exhibits a leading performance compared with literature data (Table S1).…”
Section: Resultsmentioning
confidence: 67%
“…Deep (secondary) oxidation of glyceraldehyde to GLYA has been generally known to be poor over Cu and Ni catalysts, even in the presence of externally added O 2 . 44,45 In this work, however, it is surprising to observe that all four non-noble metal catalysts display 9.6−14.2% selectivity for GLYA, even in the absence of external O 2 . It corresponds to remarkable 0.74−1.66 mol•g• mol −1 •h −1 deep oxidation rate, which exhibits a leading performance compared with literature data (Table S1).…”
Section: ■ Introductionmentioning
confidence: 67%
“…Catalysts are essential for solving the most pressing energy and environmental challenges (e.g. metal-air batteries and solid oxide fuel cells); to effectively increase catalytic reaction activity, metal nanoparticles loaded on the surface of the parent oxides can be used as a method to increase the number of active sites [1][2][3][4]. Owing to the advantages of perovskite oxides (ABO 3 ) such as high structural durability and diversity of A/B site doping components, researchers [5][6][7][8] used them as parent oxides and loaded metal nanoparticles on their surfaces to improve the catalytic performance of ABO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported utilisation of preformed H 2 O 2 as oxidant for glycerol oxidation. These studies have focussed on a range of different catalysts, including various supported metal catalysts [19][20][21][22][23][24][25] and metal oxides [26][27][28][29][30][31][32][33][34]. McMorn et al [35] assessed metal-doped silicate (containing Ti, V or Fe) and aluminophosphate catalysts (containing Cr, V, Mn or Co) for oxidation of glycerol with H 2 O 2 , reporting low yields of the desired partial oxidation products.…”
Section: Introductionmentioning
confidence: 99%